New Horizons for Precision Medicine in Biliary Tract Cancers - Valle, Juan W; Lamarca, Angela; Goyal, Lipika; Barriuso, Jorge; Zhu, Andrew X (Cancer discovery, 2017)
Biliary tract cancers (BTC), including cholangiocarcinoma and gallbladder cancer, are poor-prognosis and low-incidence cancers, although the incidence of intrahepatic cholangiocarcinoma is rising. A minority of patients present with resectable disease but relapse rates are high; benefit from adjuvant capecitabine chemotherapy has been demonstrated. Cisplatin/gemcitabine combination chemotherapy has emerged as the reference first-line treatment regimen; there is no standard second-line therapy. Selected patients may be suitable for liver-directed therapy (e.g., radioembolization or external beam radiation), pending confirmation of benefit in randomized studies. Initial trials targeting the epithelial growth factor receptor and angiogenesis pathways have failed to deliver new treatments. Emerging data from next-generation sequencing analyses have identified actionable mutations (e.g., fusion rearrangements and and mutations), with several targeted drugs entering clinical development with encouraging results. The role of systemic therapies, including targeted therapies and immunotherapy for BTC, is rapidly evolving and is the subject of this review. The authors address genetic drivers and molecular biology from a translational perspective, in an intent to offer a clear view of the recent past, present, and future of BTC. The review describes a state-of-the-art update of the current status and future directions of research and therapy in advanced BTC.